Universal Health Coverage and Facilitation of Equitable Access to Care in Africa - Sanogo, N'doh Ashken; Fantaye, Arone Wondwossen; Yaya, Sanni (Frontiers in Public Health, 2019)
Background: Universal Health Coverage (UHC) is achieved in a health system when all residents of a country are able to obtain access to adequate healthcare and financial protection. Achieving this goal requires adequate healthcare and healthcare financing systems that ensure financial access to adequate care. In Africa, accessibility and coverage of essential health services are very low. Many African countries have therefore initiated reforms of their health systems to achieve universal health coverage and are advanced in this goal. The aim of this paper is to examine the effects of UHC on equitable access to care in Africa. Methods: A systematic review guided by the Cochrane Handbook was conducted and reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses criteria (PRISMA). Studies were eligible for inclusion if 1- they clearly mention studying the effect of UHC on equitable access to care, and 2- they mention facilitating factors and barriers to access to care for vulnerable populations. To be included, studies had to be in English or French. In accordance with PRISMA guidelines, our systematic review was registered with the International Prospective Register of Systematic Reviews (PROSPERO) on April 24, 2018 (registration number CRD42018092793). Results: In all 271 citations reviewed, 12 studies were eligible for inclusion. Although universal health coverage seems to increase the use of health services, shortages in human resources and medical supplies, socio-cultural barriers, physical inaccessibility, lack of education and information, decision-making power, and gender-based autonomy, prenatal visits, previous experiences, and fear of cesarean delivery were still found to deter access to, and use of, health services. Discussion: Barriers to greater effectiveness of the UHC correspond to various non-financial barriers. There are no specific recommendations for these kinds of barriers. Generally, it is important for each country to research and identify contextual uncertainties in each of the communities of the territory. Afterwards, it will be necessary to put in place adapted strategies to correct these uncertainties, and thus to work toward a more efficient system of UHC, resulting in positive impacts on health outcomes.